Pengembangan Vidio Interaktif Fonetik Berbasis Metode Vak ( Visual, Auditori, Kinestetik ) pada Pembelajaran Membaca Permulaan di Kelas 1 SD - Maulidya Nur Affiana; Isna Khuni Mu’alimah; Khoirul Wafa (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to develop a legitimate and practical phonetic interactive film based on the Visual, Auditory, and Kinesthetic (VAK) approach to improve first-grade primary school students' beginning reading skills. The research and development (R&D) methodology of the study was based on the ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation. Research subjects were first-graders from SD Negeri Tawangsari 2 in Blitar Regency. Among the research instruments were pretest and posttest assessments, as well as validation sheets from media and material specialists. The results showed that the VAK-based phonetic interactive video achieved a very high level of validity, indicating that the product was highly valid and suitable fo. The implementation results demonstrated an improvement in children's starting reading skills based on pretest and posttest results analyzed using the N-Gain test, which fell into the medium to high range. Because of this, the VAK-based phonetic interactive movie is considered a valid, useful, and effective instructional tool to improve the starting reading skills of first-grade primary school students.